TINGKAT KEPEDULIAN SOSIAL SISWA SEKOLAH DASAR - Nur Muharromi Apriyani; Dudung Amir Soleh; Mohamad Syarif Sumantri (STKIP Persada Khatulistiwa Sintang, 2021)
The type of this research is a survey research and uses quantitative descriptive analysis. This research is conducted to obtain a description of the social care attitude of elementary school students which is one of the 18 national character values that is essential for students to have. The goal of this research is to describe the social care level of elementary school students. The instrument used in this research is a questionnaire with a likert scale. The population of this research is elementary school students in Kecamatan Kalideres and the samples are from SDN 03, SDN 09, dan SDN 12 with a total of 79 students. Samples is selected randomly. This research is conducted online considering the conditions of the Covid-19 Pandemic. Data is collected through the help of the google form application by focusing on social care variable that had been theoretically validated by two experts in the field of elementary school. Furthermore, the data is analyzed using descriptive statistics with the help of the excel program. The result of the data shows that the level of social care of students is mostly in the high category with a percentage of 64%.